DESENVOLVIMENTO E AVALIAÇÃO DE FORMULAÇÕES INOVADORAS DE GÉIS DE PERÓXIDO DE CARBAMIDA CONTENDO NANOPARTÍCULAS DE BIOVIDRO OU HIDROXIAPATITA: ESTUDO IN VITRO - Arana, Andrés Fernando Montenegro (2014)
The aim of this study was to obtain and investigate the in vitro effect of bioglass (Bv) and hydroxyapatite (HaP) nanoparticles loaded into a gel of 37.5% carbamide peroxide on mechanical properties of enamel, hydrogen peroxide permeability and tooth bleaching. The hypothesis of this study is that Bv and HaP nanoparticles can reinforce the enamel and avoid the diffusion of hydrogen peroxide to the pulp chamber, without affecting bleaching potential. Bovine teeth were obtained from Matadouro Municipal de Ponta Grossa, Paraná, Brazil, and stored into distilled water until the preparation of specimens. The specimens were randomly distributed into the experimental groups: positive control: CarbopolTM EDT2020 gel containing 37.5% carbamide peroxide without nanoparticles (37.5%PC), CarbopolTM EDT2020 gel containing 37.5% carbamide peroxide and 5% bioglass nanoparticles (37.5%+5%BvPC),CarbopolTM EDT2020 gel containing 37.5% carbamide peroxide and 5% hydroxyapatite nanoparticles (37.5% PC+5%HaP), CarbopolTM EDT2020 gel containing 5% bioglass nanoparticles (5%Bv), CarbopolTM EDT2020 gel containing 5% hydroxyapatite nanoparticles (5%HaP), negative control: CarbopolTM EDT2020 gel (CAR), a non-treated group (D). These formulations were applied in 3 sessions after 5 days from each one, during 45 min per session, divided into 3 applications of 15 min. The specimens were evaluated using morphological and chemical analyses (scanning electron microscopy, energy-dispersive Xray spectroscopy and atomic force microscopy), roughness and hardness. The permeability of peroxide hydrogen was investigated for 37.5%PC, 37.5%PC+5%Bv and 37.5%PC+5%HaP and compared to group D. An artificial pigmentation process based on red wine and black tea was used to evaluate the whitening effect of 37.5%PC, 37.5%PC+5%Bv and 37.5%PC+5%HaP. Morphological analyses confirmed the presence of particle aggregates on enamel surface for 37.5%PC+5%Bv, 5%Bv, 37.5%PC+%5HaP and 5%HaP. Only 37.5%PC showed a statistically significant reduction (p < 0.05) of hardness and roughness when the initial and final results for each group were evaluated. The bleaching effect of 37.5%PC, 37.5%PC+5%Bv and 37.5%PC+5%HaP was successfully confirmed by the use of a portable spectrophotometer. Bioglass and hydroxyapatite nanoparticles avoid enamel demineralization caused by a 37.5% carbamide peroxide gel, prevent the diffusion of hydrogen peroxide to the pulp chamber and did not affect/reduce the whitening effect of carbamide peroxide 37.5%.